Quercetin Attenuates d-GaLN-Induced L02 Cell Damage by Suppressing Oxidative Stress and Mitochondrial Apoptosis via Inhibition of HMGB1 - Fang, Peng; Liang, Jiajun; Jiang, Xuejiao; Fang, Xian; Wu, Mengli; Wei, Xiaoyi; Yang, Wenlong; Hou, Weixin; Zhang, Qiuyun (Frontiers in Pharmacology, 2020)
High mobility group box-1 (HMGB1) plays an important role in various liver injuries. In the case of acute liver injury, it leads to aseptic inflammation and other reactions, and also regulates specific cell death responses in chronic liver injury. HMGB1 has been demonstrated to be a good therapeutic target for treating liver failure. Quercetin (Que), as an antioxidant, is a potential phytochemical with hepatocyte protection and is also considered to be an inhibitor of HMGB1. However, the mechanism of its hepatoprotective effects remains to be characterized. The present study explored whether the hepatoprotective effect of Que antagonizes HMGB1, and subsequent molecular signaling events. Our results indicated that Que protects L02 cells from d-galactosamine (d-GaLN)-induced cellular damage by reducing intracellular reactive oxygen species (ROS) production and apoptotic responses in the mitochondrial pathway. Immunofluorescence and Western blot assays showed that HMGB1 was involved in d-GaLN-induced L02 cell damage. Further research showed that after transfection with HMGB1 short hairpin RNA (shRNA), cell viability was improved, and intracellular ROS production and apoptosis were suppressed. When co-treated with Que, the expression of HMGB1 was decreased significantly, the expression of proteins in the corresponding signal pathway were further reduced, and the production of ROS and apoptosis were further suppressed. Molecular docking also indicated the binding of Que and HMGB1. Taken together, these results indicate that Que significantly improves d-GaLN-induced cellular damage by inhibiting oxidative stress and mitochondrial apoptosis via inhibiting HMGB1.